1991
DOI: 10.1007/bf01351768
|View full text |Cite
|
Sign up to set email alerts
|

Entourage uniformities for frames

Abstract: Abstract. The purpose of this paper is to define a uniformity on a frame using entourages. A definition of uniformities in terms of covers has been given by A. PULTR ([8], [10]). We introduce two new symmetry conditions for a quasi-uniform space, open-set symmetry and small-set symmetry. We prove that a quasi-uniformity ~ is a uniformity if and only if it is both open-set symmetric and small-set symmetric. The category of (covering) uniform frames is isomorphic with the category of entourage uniform frames.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…A quasi-uniformity U is called proximally symmetric or Smyth symmetric [7] provided that its induced quasiproximity is a proximity. Of course, a proximally symmetric totally bounded quasi-uniformity is a uniformity.…”
Section: Infima Of Quasi-uniformitiesmentioning
confidence: 99%
“…A quasi-uniformity U is called proximally symmetric or Smyth symmetric [7] provided that its induced quasiproximity is a proximity. Of course, a proximally symmetric totally bounded quasi-uniformity is a uniformity.…”
Section: Infima Of Quasi-uniformitiesmentioning
confidence: 99%
“…In [16] Isbell introduced uniformities on frames, as the precise translation into frame terms of Tukey's notion, later developed in detail by Pultr [25]. We note that, as in the case of spaces, there are several different ways of describing uniformities on frames, such as the functional uniformities of Fletcher-Hunsaker ( [7], [8]) and the entourage unifromities of Picado [21].…”
Section: Uniform Framesmentioning
confidence: 99%
“…A frame is uniformizable provided that it admits an entourage uniformity as defined in [4]. Using the axiom of countable dependent choice, A. PULTR has shown that a flame is uniformizable if and only if it is completely regular [15,Th.…”
Section: Preliminariesmentioning
confidence: 99%
“…Definition [4]. Let L be a frame and let B be a base for a frame quasi-uniformity on L. If B satisfies:…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation